2021
DOI: 10.5194/npg-28-467-2021
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated ensemble forecasts of the height of new snow using quantile regression forests and ensemble model output statistics

Abstract: Abstract. Height of new snow (HN) forecasts help to prevent critical failures of infrastructures in mountain areas, e.g. transport networks and ski resorts. The French national meteorological service, Météo-France, operates a probabilistic forecasting system based on ensemble meteorological forecasts and a detailed snowpack model to provide ensembles of HN forecasts. These forecasts are, however, biased and underdispersed. As for many weather variables, post-processing methods can be used to alleviate these dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This excellent superiority can be attributed to the ability of QRF to learn any pattern of any response for any provided data (Dega et al, 2023). SI data is non-Gaussian and this study shows that the algorithm can be applied to both deterministic correction and probabilistic calibration of a skewed distribution of meteorological features, as claimed by Evin et al (2021). Apart from exhibiting strengths of both RFs and QR modelling, the hybrid algorithm demonstrated that it handled well the weaknesses in both QR and RF modelling separately.…”
Section: Discussionmentioning
confidence: 63%
“…This excellent superiority can be attributed to the ability of QRF to learn any pattern of any response for any provided data (Dega et al, 2023). SI data is non-Gaussian and this study shows that the algorithm can be applied to both deterministic correction and probabilistic calibration of a skewed distribution of meteorological features, as claimed by Evin et al (2021). Apart from exhibiting strengths of both RFs and QR modelling, the hybrid algorithm demonstrated that it handled well the weaknesses in both QR and RF modelling separately.…”
Section: Discussionmentioning
confidence: 63%
“…However, that study did not consider the uncertainties associated with phase partitioning. Evin et al (2021) highlighted the poor performance in snowpack accumulation simulations due to errors in phase partitioning. In our study, when focusing on all the accumulation events and the warm events, the PPM type greatly impacted SWE accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Because although static experiments use fixed climatology as predictors, the samples are relatively evenly distributed (i.e., homogeneous). However, the homogeneity of Analog experiments was degrading heavily (Evin et al., 2021). Dynamic experiments exhibited the best performance and played an unbeatable role, which confirms the importance of near‐real‐time predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that the QRF model performs better than EMOS and can bring additional value to the human forecaster. Evin et al (2021) proposed using the QRF model to calibrate ensemble forecasts of the height of new snow, which also indicated that QRF could be applied to the correction of skewed distribution for variable similar to precipitation. In addition to the post-processing of MWPs, QRF has also been successfully applied to hydrological ensemble post-processing (Tyralis & Papacharalampous, 2021;Tyralis et al, 2019) and soil uncertainty mapping (Kasraei et al, 2021;Vaysse & Lagacherie, 2017).…”
mentioning
confidence: 99%